The effect of differentiated learning and independence learning on the development of religious competencies of grade v students of sentosa elementary school, medan perjuangan - Winda Yani Hrp; Siti Halimah; Haidir (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to analyze: (1) the effect of differentiated learning on students' religious competence, (2) the effect of independence on students' religious competence, and (3) the effect of differentiated learning and independent learning together on students' religious competence. The research method used is a quantitative approach with a correlational research type. The population in this study were all fifth-grade students of Sentosa Elementary School, Medan Perjuangan, totaling 30 students using a total sampling technique. The results of the study indicate that: (1) differentiated learning has a positive and significant effect on students' religious competence with a significance value of 0.025 < 0.05, so that the first hypothesis (Ha) is accepted. (2) independence does not have a significant effect on students' religious competence with a significance value of 0.797 > 0.05, so that the second hypothesis (Ha) is rejected, although the resulting relationship remains positive with a contribution of 4.7%; and (3) differentiated learning and independence simultaneously have a significant effect on students' religious competence with a significance value of 0.045 < 0.05, so that the third hypothesis (Ha) is accepted. The coefficient of determination (R²) value of 0.205 indicates that the two variables simultaneously contribute 20.5% to students' religious competence, while the remaining 79.5% is influenced by other factors outside the study. This study provides theoretical and practical implications, adds to scientific studies and serves as a reference in the field of Islamic Religious Education. Recommendations: Further research is recommended to use a larger sample size and apply mixed research methods to ensure more accurate and more widely generalizable research results.